Determinants of the High-tech Sector Innovation Performance in the European Union: A Review. (2015) - Baesu, Viorica; Albulescu, Claudiu Tiberiu; Farkas, Zoltan-Bela; Drăghici, Anca
Abstract: The purpose of the paper is to analyze the determinants of the high-tech sector innovation performance in the European Union (EU) countries. The innovation performance is assessed through patents applications, granted patents and trade mark applications. We resort to a panel data approach, comparing the results of a fixed effects model and a random effects model, for the period 1994-2011. Our findings show that the number of employees in the high-tech industry positively influences the number of patents while the R&D expenditure per capita has a negative impact. Other factors like the expenditure on education, the government R&D expenditure, the economic development, the number of employees in the science and technology field and the exports' level, have no influence on the innovation performance in the high-tech industry. However, when we assess the innovation performance through community trade mark applications, we discover that most of the above mentioned factors can be considered as determinants of the innovation performance. The obtained results are robust regarding different empirical models used in our analysis.